Influence of different types of organic amendments on soil remediation and performance of maize grown on a lead contaminated soil. (2012)
Accumulation of heavy metals in agricultural soils rcsults in long term environmental problem, elevateci heavy metal uptake by crops and food poisoning. Remediation of sites contaminateci by heavy metals is therefore pertinent. Incubation and greenhouse studies were conducted to test for thè effects of different types of compost on soil remediation and thè growth of maizc planted on rcmediated battery wastes contaminated soil. Composts made from five different plani materials (Soyabean stover (SS), Maize Stover (MS), Mexican Sunflower (SW), Cassava Wastes (CW) and Neem Seeds (MS) as well as Poultry Manure (PM) alone and Organo-mineral fertilizer (OM) were used. Each was applied at thè rate of 20 t/ha. Pre-cropping soil Chemical compositions showed that lead concentration (148000 mg/kg) was significantly higher than thè permissible level (300 mgkg1) at thè study site. Results of incubation studies revealed a progressive reduction in heavy metal concentrations for thè sampling periods. MSW and CW composts significantly reduced soil lead by 39% and 38% respectively followed by SS (33%), MS (28%), PM (26%), NS (25%) and OM (23%). Application of compost to thè contaminated soil also enhanced vegetative growth of maize when compared with control. SS, CW, NS, MS, MSW, OM, and PM increased thè dry matter yield by 49%, 60%, 56%, 24%, 68% , 55% and 27% respectively over control. Unlike thè maize plants grown on organic amendcd contaminated soil, control Dlants started showing toxicity symptoms such as necrotic lesions, chlorosis, wilting and eventual death. Organic imendment also increased nutrients uptake by maize crop compared to control plants. Generally organic amendments proved effective in remediation of heavy metal contaminated soil and had ameliorative effects on crop growing on contaminated soil. Among thè organic amendments, MSW and CW performed better.